2016
DOI: 10.1080/2162402x.2016.1160186
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating HLA-matched CD4+T cells retargeted against Hodgkin and Reed–Sternberg cells

Abstract: Hodgkin lymphoma (HL) presents with a unique histologic pattern. Pathognomonic Hodgkin and Reed-Sternberg (HRS) cells usually account for less than 1% of the tumor and are embedded in a reactive infiltrate mainly comprised of CD4(+) T cells. HRS cells induce an immunosuppressive microenvironment and thereby escape antitumor immunity. To investigate the impact of interactions between HRS cells and T cells, we performed long-term co-culture studies that were further translated into a xenograft model. Surprisingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Both the possibility of antigen presentation from Hodgkin-Reed-Sternberg cells to the T cells, 27,28 as well as a host-anti-lymphoma response have been discussed. [29][30][31] When T FH markers such as PD1 became available, it became clear that the rosetting T cells in NLPHL and the lymphocyterich classic HL differ from the other subtypes of HL, as they represent T FH cells. 11 In the present study, we confirmed the presence of PD1 + rosetting T cells at similar frequencies in both typical and variant growth pattern NLPHL, and additionally observed that these T cells frequently express CD69.…”
Section: Discussionmentioning
confidence: 99%
“…Both the possibility of antigen presentation from Hodgkin-Reed-Sternberg cells to the T cells, 27,28 as well as a host-anti-lymphoma response have been discussed. [29][30][31] When T FH markers such as PD1 became available, it became clear that the rosetting T cells in NLPHL and the lymphocyterich classic HL differ from the other subtypes of HL, as they represent T FH cells. 11 In the present study, we confirmed the presence of PD1 + rosetting T cells at similar frequencies in both typical and variant growth pattern NLPHL, and additionally observed that these T cells frequently express CD69.…”
Section: Discussionmentioning
confidence: 99%
“…However, an anti-HRS cell activity of CD4 þ T cells against HL cell lines in coculture becomes detectable only after about 6 days of culture (34). Gene expression profiling revealed that after 7 days of coculture with the cHL cell line L428, HLAmatched and -unmatched CD4 þ T cells showed similar changes in their gene expression (34). Hence, the influence of HRS cells on cocultured CD4 þ T cells is stronger than effects through a mismatched MHC class II.…”
Section: Purinergic Signaling In Chlmentioning
confidence: 97%
“…As CD4 þ T cells were not HLA matched, a potential influence of HLA mismatching on the behavior of the CD4 þ T cells must be considered. However, an anti-HRS cell activity of CD4 þ T cells against HL cell lines in coculture becomes detectable only after about 6 days of culture (34). Gene expression profiling revealed that after 7 days of coculture with the cHL cell line L428, HLAmatched and -unmatched CD4 þ T cells showed similar changes in their gene expression (34).…”
Section: Purinergic Signaling In Chlmentioning
confidence: 99%
“…They display three independent patient cases, as they were derived from pleural effusions (KM-H2, L-428) or peripheral blood (L-1236), and cover two different subtypes of HL, namely nodular sclerosis (L-428) and mixed cellularity (KM-H2, L-1236). A preclinical model reflecting the low abundance of tumor cells within the affected tissue is therefore so far not available [ 29 , 30 ]. Hence, we have assessed VSV-CD30 in a mouse model of disseminated growing cHL tumor cells and found a substantial reduction in tumor growth at least for some of the mice.…”
Section: Discussionmentioning
confidence: 99%
“…Envelope modification as done here, however, has often resulted in attenuation of VSV [ 34 ]. Upon completion, VSV-CD30 will add to a growing list of CD30-targeted therapeutics that include besides antibodies also CD30-specific AAV vectors [ 35 ] and CAR T cells [ 30 , 36 ]. Combining VSV-CD30 with these or other cancer therapeutics such as checkpoint inhibitors will be another future option to be explored.…”
Section: Discussionmentioning
confidence: 99%